Pertumbuhan dan Produksi Kedelai (Glycine max L. Merr) pada Pemberian Pupuk Organik dan Cekaman Air - A Aminah (Fapetrik-UMPAR, 2020)
This research aims to study the effect of using organic fertilizers on the growth and yield of soybeans. Besides, to study the selection of the best types of organic fertilizers to increase the soil's ability to absorb water so that it can increase yield even in drought conditions. The research was carried out in the Faculty of Agriculture screen house, Indonesian Muslim University, Makassar, with the type of alfisol soil. The design used as factorial based on a randomized block design, which consisted of 2 factors. The first factor is the use of organic fertilizers, namely without organic fertilizers (P0), chicken manure (P1), Azolla compost (P2), and bokashi waste (P3). The second factor is the quantity of water supply, namely 350 mm/season (Al), 450 mm/season (A2), and 550 mm/season (A3). The results showed an interaction between the type of organic fertilizer and the amount of water supply on the total dry weight of the plant at harvest, the number of seeds, and the percentage of seed success. The enormous total dry weight of plants and the largest number of sources occurred in the combination of giving chicken manure and a water supply of 550 mm/season. Meanwhile, the highest percentage of seeds was in the variety of Azolla fertilizer treatment and water supply of 350 mm/season. The water supply treatment also significantly affects plant height, the number of leaves, and plants' total dry weight. Simultaneously, the yield components, namely the dry weight of seeds and the weight of 100 seeds with a water supply of 550 mm/season produced the best results.